Urban Metro Elevated Station to Generate Solar Power - Rajendran, Lallendran; T. Thirugnana, Sathiabama (International Journal of Integrated Engineering, 2018)
This paper is focused to understand the practicality and projected analysis to utilize urban metro elevated stations as solar electricity power generation by utilizing the roof area in m2 for solar panel installation to generate electricity based on renewable and sustainable energy. Mass Rapid Transit Klang Valley Line 1 of Kuala Lumpur, Malaysia has been selected for this research study. Ultimately this will help to mitigate environmental issues and helps to contribute current electricity demand load challenges faced by energy service providers. Solar power works at maximum output with favorable parameters and Kuala Lumpur has an annual average of solar irradiance of 4.9 kWh/m2/day, ambient temperature 25.53Â°C, wind speed 2.24 m/s and air mass (A.M) 1.5. In addition, urban metro elevated stations roof area for stations can be utilized by installing solar panels which indirectly able to bring revenue collection to stakeholders. Some of the key challenges in this research are selection of the best solar panels, inverters and medium voltage stations including the return on investment (ROI).